(untitled) (The Science Post, 2025)
Heart disease continues to be the leading cause of mortality worldwide, presenting significant challenges to healthcare systems, especially in aging populations and those with sedentary lifestyles. Technological innovation has introduced powerful tools that are transforming how cardiovascular diseases are prevented, diagnosed, and managed. This paper presents a theoretical framework that integrates systems theory, socio-technical theory, and the Health Belief Model to evaluate how emerging technologies contribute to the evolving landscape of heart disease care. By aligning theory with innovation, we explore the potential of technology to enhance patient outcomes, clinical efficiency, and long-term disease prevention strategies.